Learning from History para doxan: a New Approach to Polybius’ Manifold View of the Past - Maier, Felix K. (Histos, 2012)
Scholars have seen a contradiction in Polybius’ view of history because, on the one hand, he talks of cycles and recurrent actions, but on the other is aware of the unpredictable aspects of history (as seen, e.g., with tychê). The present paper seeks to show that there is no contradiction in Polybius’ thought, since alongside the belief that the future can be deduced by drawing logical (κατὰ λόγον) conclusions from the past, there is another strand in Polybius which recognizes and indeed highlights the importance of contingency in history, and the fact that many events occur contrary to human reckoning (παρὰ λόγον). Although Polybius does not discuss the latter explicitly, he nonetheless underscores it by the use of counterfactual thinking and of narratives that emphasize accidental occurrences. Both approaches serve, although in different ways, the paideutic purposes of Polybius’ work.